2006
DOI: 10.1021/ac052143f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Biosensor Based on Integrated Assembly of Dehydrogenase Enzymes and Gold Nanoparticles

Abstract: Development of a highly sensitive nanostructured electrochemical biosensor based on the integrated assembly of dehydrogenase enzymes and gold (Au) nanoparticle is described. The Au nanoparticles (AuNPs) have been self-assembled on a thiol-terminated, sol-gel-derived, 3-D, silicate network and enlarged by hydroxylamine seeding. The AuNPs on the silicate network efficiently catalyze the oxidation of NADH with a decrease in overpotential of approximately 915 mV in the absence of any redox mediator. The surface ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(139 citation statements)
references
References 65 publications
3
134
0
2
Order By: Relevance
“…The catalytic effect of GNPs was explained by the oxidation effect of surface oxides, which originated from the unusually oxidation of GNPs at low potential. A more detailed study similar to this case was reported by the same group later [115]. Nitric oxide electrochemical sensors fabricated on GNPs modified platinum microelectrode [116] or dense GNP film modified electrode [117] were also reported to be based on the catalytic oxidation of GNPs.…”
Section: Gnps Act As Electrocatalystsupporting
confidence: 75%
“…The catalytic effect of GNPs was explained by the oxidation effect of surface oxides, which originated from the unusually oxidation of GNPs at low potential. A more detailed study similar to this case was reported by the same group later [115]. Nitric oxide electrochemical sensors fabricated on GNPs modified platinum microelectrode [116] or dense GNP film modified electrode [117] were also reported to be based on the catalytic oxidation of GNPs.…”
Section: Gnps Act As Electrocatalystsupporting
confidence: 75%
“…GNP based glucose biosensors have a detection limit of 0.18 μM (Andreescu & Luck 2008). A NADH sensor based on GNPs shows 780 mV potential decreases without any electron transfer mediators (Jena & Raj 2006). Piezoelectric biosensors are principally based on changes in mass.…”
Section: Nanoparticle Based Biosensorsmentioning
confidence: 99%
“…Currently, a (3-mercaptopropyl)-trimethoxysilane (MPTS) sol-gel-derived three-dimensional network is attractive in the development of sensing devices. The thiol tail groups of an MPTS three-dimensional network is able to be covalently bound onto the surface of Au through cleavage of the S-H bond 17 and the formation of a Au-S bond, 18 while AuNPs can be conveniently self-assembled on the thiol groups present in the network. MPTS sol-gel and AuNPs-based materials have been used for the immobilization of enzymes, such as dehydrogenase, 17,19 bilirubin oxidase, 20 lactate oxidase 21 and glucose oxidase, 22 for the development of biosensors.…”
Section: Introductionmentioning
confidence: 99%